A meta‐analysis of the effectiveness of Yangxue Qingnao granules for the treatment of chronic cerebral circulation insufficiency. Issue 5 (31st March 2020) - Jia, Yujuan; Wang, Jie; Hou, Yuli
Abstract: Objective: Yangxue Qingnao granules (YXQNG), which translates to granules that tonify the blood and clear liver heat, are widely available in China for the treatment of Chronic Cerebral Circulation Insufficiency (CCCI). This systematic review aimed to evaluate the effectiveness and safety of YXQNG in treating CCCI. Methods: PubMed, the Cochrane Central Register of Controlled Trials, Embase, the Chinese National Knowledge Infrastructure, and the Wanfang Database were searched from their inception to February 2019. Randomized controlled trials of YXQNG used alone or in combination with other drugs against a placebo, with no intervention or used with other drugs in CCCI patients were identified. The reviewers identified studies, extracted data, and assessed the quality of the evidence, independently and in duplicate. The Cochrane risk of bias assessment tool was used for quality assessment. Results: A total of 31 RCTs and 2, 877 patients were selected. The meta‐analysis indicated that the ratio between the combined RR of the total effective rate and the 95% confidential interval (95% CI) was 1.21 (1.17, 1.26). The combined MD of transcranial Doppler (TCD) detecting carotid artery, vertebral artery, and basilar artery blood flows (95% CI), respectively, were 8.84 (5.83, 11.85), 4.72 (3.71, 5.73), and 3.89 (3.03, 4.76). The combined MD of plasma viscosity and fibrinogen, respectively, were −0.35 (−0.40, −0.30) and −0.81 (−1.12, −0.50). Serious adverse effects were not reported in all the included trials. Conclusion: This systematic review revealed that YXQNG could increase cerebral blood flow in patients with CCCI and improve their symptoms, with no serious adverse effects. Since the literature reviewed was affected by factors such as lower quality of the included studies, the systematic evaluation's conclusion is not very reliable. Thus, more rigorously designed trials are needed. Abstract : Yangxue Qingnao granules (YXQNG), which translates to granules to tonify blood and clear liver heat, are widely available in China for treating Chronic Cerebral Circulation Insufficiency (CCCI). This systematic review aims to evaluate the effectiveness and safety of YXQNG in treating CCCI.